Potential predation and fecundity of Amblyseius aerialis fed two-spotted spider mite - Maciel, Anilde da Graça Sousa; Trindade, Roseane Cristina Predes; Silva, Edmilson Santos; dos Santos, Márcia Daniela (Comunicata Scientiae, 2019)
The mites of the Phytoseiidae family stand out for the biological control of pest mites. The species Amblyseius aerialis (Muma, 1955) is a generalist mite, which can contribute to the natural regulation of pest mites. The objective of this study was to evaluate the potential for predation and fecundity of A. aerialis on the different phases of Tetranychus urticae (Koch, 1836) (Acari: Tetranychidae). A female of A. aerialis was confined on dish (3.0 cm in diameter) of jack bean leaves, Canavalia ensiformis (L.) DC. The discs were left in petri dish with water. Each T. urticae phase was offered individually to A. aerialis at densities: 2, 5, 10, 15, 20 and 30 mites / arena. The number of prey consumed and eggs laid by A. aerialis were evaluated every 24 hours for seven days, with removal of laid eggs by phytoseiid and dead prey and replacement of prey in the initial amount. The data were submitted to analysis of variance and the means were compared by Tukey test, applying the factorial (4x6). It was observed that with the increase of the density of T. urticae offered there was an increase in the predation of A. aerialis. When offered the nymph and adult the average number of eggs per day was higher, differing from egg and larva. Thus, A. aerialis can be a biological control agent of the T. urticae, reducing the population of the pest and maintaining its fecundity in all phases and densities offered.